Importancia del tipo de cambio en las importación de productos químicos (2021)
What is going to be exposed in this work is the different incidences that the exchange rate has in the imports of chemical products in Colombia, taking into account exchange risks, the volatility of the Colombian currency, and the process used by some companies in the sector. chemical when importing the product. The methodology used to prepare the document was descriptive, due to the fact that information was collected from different academic databases, in addition to various government agencies and other digital resources such as articles or news.